SOCIAL CRITICISM IN FAHD DJIBRAN'S IMPERFECT NOVEL A SOCIOLOGY OF LITERATURE REVIEW - Novianti, Hasmi; Febrina, Liga (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
This study describes the background of social criticism in Fahd Djibran's novel Tak Sempurna using a sociology of literature review. The author's interest in the science of social criticism, in this case, the sociology of literature related to social life in educational issues that exist in Indonesian society. The social life of society written in the literary work of the novel is what the author wants to reveal in this study. The purpose of this study is to reveal the social criticism contained in the novel Tak Sempurna by Fahd Djibran with a literary sociology approach, especially the sociology of literary works.describing social attitudes and social behavior in the novel. This research uses the hermeneutic or interpretation method. The object of this research is the novel Tak sempurna by Fahd Djibran.Published in 2013, by the publisher Kurniaesa Publishing, published in Yogyakarta.The focus of this research is social criticism in the novel Tak Sempurna by Fahd Djibran with a review of literary sociology, which looks in terms of social attitudes and social behavior in the novel.Then it can be understood that the data of this study were collected descriptively.Data analysis techniques in the application of the interpretation method, researchers emphasize the hermeneutics developed by Paul Ricoeur.